Changes in Bacillus anthracis CodY regulation under host-specific environmental factor deprived conditions. (December 2016) - Kim, Se; Jung, Kyoung; Chai, Young
Abstract Background Host-specific environmental factors induce changes inBacillus anthracis gene transcription during infection. A global transcription regulator, CodY, plays a pivotal role in regulating central metabolism, biosynthesis, and virulence inB. anthracis . In this study, we utilized RNA-sequencing to assess changes in the transcriptional patterns of CodY-regulatedB. anthracis genes in response to three conditions of environmental starvation: iron, CO2, or glucose deprivation. In addition, we performed chromatin immunoprecipitation on newly identified CodY-mediated genes. Results Environmental deprivation induced transcriptional changes in CodY-regulated genes in both wild-type andcodY null strains, and both CodY-specific and environment-specific patterns were observed. In the iron-depleted condition, overexpression of iron homeostasis genes was observed independent ofcodY deletion; however, transcription of siderophore and amino acid biosynthesis genes was CodY dependent. Although CodY has a significant regulatory role in central metabolism and the carbon overflow pathway, metabolism-associated genes exhibited CodY-independent expression patterns under glucose starvation. Genes that were differentially expressed in response to CO2 availability showed CodY-dependent regulation, though their maximal expression did require a supply of CO2 /bicarbonate. Conclusions We speculate that CodY regulates the expression of environmental-responsive genes in a hierarchical manner and is likely associated with other transcription regulators that are specific for a particular environmental change.